2016
DOI: 10.32404/rean.v3i2.1107
|View full text |Cite
|
Sign up to set email alerts
|

Production of 'Formosa' Papaya Seedlings in Different Protected Environments and Organic Substrates

Abstract: It is aimed to evaluate the effect of cattle manure, and ground crushed cassava branches based substrates in the growth of 'Formosa' papaya seedlings under different environmental conditions. Four protected environments were tested: greenhouse in arched, covered with polyethylene film with a thermo reflective screen underneath it; similar greenhouse but without the reflective screen; monofilament nursery with 50% shade screen and thermo reflective nursery with 50% shade screen. In the protected environments, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Besides reducing sunlight direct incidence on plants by shading with a cover, the protected environment can favor microclimate conditions, protect against pests, and decrease evapotranspiration, strengthening seedlings. Studies have demonstrated that plant species interact differently when under certain shading levels, which can provide seedlings of different sizes (Costa et al, 2017;Cruz et al, 2016;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides reducing sunlight direct incidence on plants by shading with a cover, the protected environment can favor microclimate conditions, protect against pests, and decrease evapotranspiration, strengthening seedlings. Studies have demonstrated that plant species interact differently when under certain shading levels, which can provide seedlings of different sizes (Costa et al, 2017;Cruz et al, 2016;Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…En un período de menor precipitación, la caseta agrícola con pantallas negras y aluminizadas, en comparación con el invernadero agrícola con película de polietileno, proporciona a las plántulas de papaya del grupo 'Sunrise solo' con mayor altura y número de hojas (Costa et al, 2010), y plántulas de mayor calidad para el grupo 'Formosa' (Santos et al, 2016) y mayor materia seca en una caseta agrícola con pantalla de aluminio para el grupo 'Sunrise solo' (Costa et al, 2009). En períodos de mayor precipitación, el invernadero, en comparación con las pantallas, permite plantas más grandes con mayor número de hojas (Costa et al, 2011).…”
Section: Introductionunclassified
“…Many factors can affect seedling quality especially the conditions under which they are produced and the substrate source (Santos et al, 2018). According to Terra et al (2011) and Santos et al, (2016), the ideal substrate for seedling production must have a good structure, allowing aeration, water availability and nutrient retention, adequate pH, pathogens free and stimulation of the high dry weight content production in both the aerial and root parts. Besides the physical, chemical and sanitary characteristics of substrates, cost/benefit ratio, availability in the market and handling must be taken into account (Silva et al, 2011;Ahmed et al, 2013;Dahmardeh, 2013).…”
Section: Introductionmentioning
confidence: 99%